Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.5 - Rationalizing Numerators and Denominators of Radical Expressions - Practice: 5

Answer

$\frac{\sqrt[5] {a^{2}b^{3}}}{2b^{3}}$

Work Step by Step

First we simplify the expression: =$\frac{\sqrt[5] {a^{2}}}{\sqrt[5] {32b^{12}}}$ =$\frac{\sqrt[5] {a^{2}}}{\sqrt[5] {2^{5}\times b^{10+2}}}$ =$\frac{\sqrt[5] {a^{2}}}{\sqrt[5] {2^{5}\times b^{10}\times b^{2}}}$ =$\frac{\sqrt[5] {a^{2}}}{2b^{2}\times \sqrt[5] {b^{2}}}$ Next, we rationalize the denominator: =$\frac{\sqrt[5] {a^{2}}}{2b^{2}\times \sqrt[5] {b^{2}}}\times\frac{ \sqrt[5] {b^{3}}}{ \sqrt[5] {b^{3}}}$ =$\frac{\sqrt[5] {a^{2}}\times\sqrt[5] {b^{3}}}{2b^{2}\times \sqrt[5] {b^{2}}\times\sqrt[5] {b^{3}}}$ =$\frac{\sqrt[5] {a^{2}b^{3}}}{2b^{2}\times \sqrt[5] {b^{5}}}$ =$\frac{\sqrt[5] {a^{2}b^{3}}}{2b^{2}\times b}$ =$\frac{\sqrt[5] {a^{2}b^{3}}}{2b^{3}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.